Proopiomelanocortin neuron manipulation in mouse models of energy balance disorders - Daimon, Caitlin Mieko, author; Hentges, Shane, advisor; Clay, Colin, committee member; Myers, Brent, committee member; Vandewoude, Susan, committee member (Colorado State University. Libraries, 2021)
Proopiomelanocortin (POMC) neurons in the arcuate nucleus (ARC) of the hypothalamus are critical regulators of energy balance. Highly conserved amongst mammalian species, POMC neurons release peptide transmitters to help an organism maintain appropriate levels of food intake and bodyweight by inhibiting feeding and facilitating metabolism of consumed nutrients. Disruptions in POMC signaling are thought to underlie aspects of energy balance disorders. There are two kinds of energy balance disorders: those of positive energy balance, which includes diseases like obesity, and those of negative energy balance, which includes eating disorders like anorexia nervosa (AN). Given that POMC neurons are believed to be dysregulated in energy balance disorders, treatment strategies for these disorders have focused on POMC neurons or their targets. The goal of the studies discussed herein was to determine whether manipulation of POMC neurons could improve pathophysiological alterations in bodyweight and food intake in mouse models of energy balance disorders. Mouse models of AN and obesity were used in the current studies. AN was mimicked in the mouse via the well-validated activity-based anorexia (ABA) behavioral paradigm. The results shown in chapters 2 and 3 indicate that POMC neurons are selectively involved in generating food anticipatory activity (FAA) in mice undergoing ABA as disruption of either the POMC peptide product β-endorphin or inhibition of the entire POMC neuron resulted in decreased FAA. As FAA is the primary output of the food entrainable oscillator (FEO), the circadian clock that allows an organism to anticipate the daily arrival of meals, these results suggest that POMC neurons via the peptide product β-endorphin are possibly involved in the expression of the FEO. As the identity of the FEO has yet to be determined, future studies should further characterize the contribution of β-endorphin and POMC neurons to the FEO. To determine whether manipulation of POMC neurons is beneficial in a mouse model of obesity, mice fed an obesogenic diet were subjected to chronic POMC neuron stimulation for one month. The unexpected finding that sustained stimulation leads to weight gain as opposed to weight loss indicates that chronic stimulation of POMC neurons may not be a viable option for weight loss, at least under the dosing scheme used in the current study. How POMC neurons adapt to chronic stimulation remains unknown and should be the focus of future work.
Keywords: bodyweight; food intake; energy balance disorders; anorexia nervosa; obesity